1966
DOI: 10.3758/bf03328083
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and delayed retention, arousal, and the orienting and defensive reflexes

Abstract: Contrary to implications of previous paired-associate learning studies and Walker's theory, high arousal words showed superior immediate as well as delayed retention. GSRs were reliably greater for the high than the low arousal words. High arousal words also evoked reliably greater cephalic vasoconstriction, defensive reflexes, than low arousal words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 4 publications
(5 reference statements)
6
38
0
Order By: Relevance
“…The extroverts who learned the list to criterion significantly faster than the introverts did not have SignifICantly higher recall scores even at the immediate retention interval. The criterion for learning the list was deliberately set at less than perfect learning to allow for any reminiscence effects, but little was found except at the immediate recall interval A recent study (Maltzman, Kantor, & Langdon, 1966) has questioned the research fmdings of Kleinsmith, Kaplan, Walker, et al, and has argued that there is a confounding of arousal during learning and retention. Kaplan & Kaplan ( 1968) have answered this argument showing that the GSRs which were used to measure arousal at training, did not correlate with the GSRs at the time of recall.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…The extroverts who learned the list to criterion significantly faster than the introverts did not have SignifICantly higher recall scores even at the immediate retention interval. The criterion for learning the list was deliberately set at less than perfect learning to allow for any reminiscence effects, but little was found except at the immediate recall interval A recent study (Maltzman, Kantor, & Langdon, 1966) has questioned the research fmdings of Kleinsmith, Kaplan, Walker, et al, and has argued that there is a confounding of arousal during learning and retention. Kaplan & Kaplan ( 1968) have answered this argument showing that the GSRs which were used to measure arousal at training, did not correlate with the GSRs at the time of recall.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…For example, Kleinsmith and Kaplan (1963) reported that on a delayed test, high-arousal words such as RAPE and VOMIT were remembered better than were low-arousal words. Maltzman, Kantor, and Langdon (1966) provided evidence that the physiological response to such stimuli was a defensive response, not an orienting response.…”
Section: Relatedmentioning
confidence: 99%
“…As compared with neutral words, words associated with sex and the bathroom were well remembered, whereas words associated with violence were remembered at the same level as the neutral words (Manning & Goldstein, 1976). Taboo words (e.g., vulgar sexual references and racial taunts) appear to be especially potent, leading to changes in skin conductance (Walker & Tarte, 1963) and vasoconstriction indicative of defensive responses (Maltzman et al, 1966). Kensinger and Corkin (2003) demonstrated that taboo words led to greater recognition than did both negative-affect emotional words and neutral words.…”
mentioning
confidence: 99%
“…Early researchers investigated paired-associate memory for emotional words, with much of their focus on whether the superior recall of emotional over neutral words required a delayed retention test (Kleinsmith & Kaplan, 1963, 1964Maltzman, Kantor, & Langdon, 1966). However, experimental design emerged as a moderating factor in the influence of emotion on memory (Walker & Tarte, 1963).…”
mentioning
confidence: 99%